Budaya Patronase di Indonesia: Tinjauan Medan Politik dan Modal Sosial dalam Teori Praktik Sosial Bourdieu (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The culture of patronage is a key characteristic of Indonesian political dynamics, having developed from the pre-colonial era to the contemporary democratic era. Despite decentralization and political reforms in Indonesia, patronage practices persist through relationships between political elites, bureaucracy, business actors, and communities, particularly at the local level. This study analyzes patronage using Pierre Bourdieu's Social Practice Theory framework, which emphasizes the interaction between habitus, capital, and the arena as factors shaping social practices. The method used is descriptive qualitative research with data collection techniques through desk studies, which allows researchers to examine various academic literature to build a comprehensive conceptual analysis. The research findings indicate that internalized political habitus, the accumulation of economic, social, cultural, and symbolic capital, and a competitive local political field are key elements in perpetuating patronage. Patronage is not merely a transactional political practice, but a social structure that is continuously reproduced and impacts the politicization of bureaucracy, the strengthening of oligarchy, power inequality, and the vulnerability of the poor to political manipulation. This research confirms that efforts to strengthen democracy in Indonesia require transformation of the political habitus of society, bureaucratic reform, and restrictions on the dominance of economic actors in the political arena to break the entrenched patron-client chain.